2011
DOI: 10.1055/s-0031-1280473
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial Alkaloids from the Stem Bark ofStrychnos malacoclados

Abstract: From the stem bark of Strychnos malacoclados, one new bisindole alkaloid, 3-hydroxylongicaudatine Y (1), was isolated along with the known alkaloids vomicine (2), bisnordihydrotoxiferine (3), divarine (4), longicaudatine (5), longicaudatine Y (6), and longicaudatine F (7). All the compounds were tested for their antimalarial activity against the chloroquine-sensitive 3D7 and -resistant W2 strains of Plasmodium falciparum. Longicaudatine was the most active compound with IC₅₀ values of 0.682 and 0.573 µM, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…A cytotoxicity assay on WI-38 human fibroblasts with the most active 90 showed that the antiplasmodial activity is not specific. However, the structurally similar longicaudatine F ( 91 ), possessing an open ring in place of the six-membered oxygen heterocycle in 90 , was 40 times more selective against the parasite, despite the slightly lower antiplasmodial activity [76]. A phytochemical investigation of Strychnos icaja root provided a new bisindole, strychnobaillonine ( 93 ), and the known strychnohexamine ( 94 ) (Fig.…”
Section: Alkaloidsmentioning
confidence: 99%
“…A cytotoxicity assay on WI-38 human fibroblasts with the most active 90 showed that the antiplasmodial activity is not specific. However, the structurally similar longicaudatine F ( 91 ), possessing an open ring in place of the six-membered oxygen heterocycle in 90 , was 40 times more selective against the parasite, despite the slightly lower antiplasmodial activity [76]. A phytochemical investigation of Strychnos icaja root provided a new bisindole, strychnobaillonine ( 93 ), and the known strychnohexamine ( 94 ) (Fig.…”
Section: Alkaloidsmentioning
confidence: 99%
“…The crude extract and the isolated compounds of this plant were evaluated for their ability to inhibit the 3D7 strain of Plasmodium falciparum and were evaluated to treat liver complaints and to facilitate the production of breast milk [20,21]. Phytochemical studies of A. klaineanum extracts have shown the presence of secondary metabolites with antimalarial properties [22]. As of now, very few authors reported the evaluation of the antioxidant and antiinflammatory activities of the recipe from these plant.…”
Section: Introductionmentioning
confidence: 99%
“…During previous works on the roots and stem bark of S. icaja , , a minor alkaloid giving a persistent red coloration after spraying with cerium sulfate reagent was identified, but could not be isolated due to a limited amount of the extracts. In a continuation of our search for potential antiplasmodial compounds from Strychnos species, we reinvestigated the tertiary alkaloids of S. icaja to isolate this minor alkaloid and evaluate its antiplasmodial activity. The targeted alkaloid, named strychnobaillonine ( 1 ), was successively isolated together with sungucine, bisnordihydrotoxiferine, and strychnohexamine ( 2 ), previously isolated from the plant. , Compounds 1 and 2 were tested in vitro against the chloroquine-sensitive 3D7 strain of P. falciparum .…”
mentioning
confidence: 99%